Ethnoracial differences in Alzheimer's disease from the FLorida Autopsied Multi‐Ethnic (FLAME) cohort. Issue 5 (18th February 2019) - Santos, Octavio A.; Pedraza, Otto; Lucas, John A.; Duara, Ranjan; Greig‐Custo, Maria T.; Hanna Al‐Shaikh, Fadi S.; Liesinger, Amanda M.; Bieniek, Kevin F.; Hinkle, Kelly M.; Lesser, Elizabeth R.; Crook, Julia E.; Carrasquillo, Minerva M.; et al.
Abstract: Introduction: Our primary goal was to examine demographic and clinicopathologic differences across an ethnoracially diverse autopsy‐confirmed cohort of Alzheimer's disease cases. Methods: A retrospective study was conducted in the Florida Autopsied Multi‐Ethnic cohort on 1625 Alzheimer's disease cases, including decedents who self‐reported as Hispanic/Latino (n = 67), black/African American (n = 19), and white/European American (n = 1539). Results: Hispanic decedents had a higher frequency of family history of cognitive impairment (58%), an earlier age at onset (median age of 70 years), longer disease duration (median of 12 years), and lower MMSE proximal to death (median of 4 points) compared with the other ethnoracial groups. Black decedents had a lower Braak tangle stage (stage V) and higher frequency of coexisting hippocampal sclerosis (21%); however, only hippocampal sclerosis differences survived adjustment for sex, age at onset, and disease duration. Neither Thal amyloid phase nor coexisting Lewy body disease differed across ethnoracial groups. Discussion: Despite a smaller sample size, Hispanics demonstrated longer disease duration with Alzheimer's disease, but not greater lifespan. Neuropathologic differences across ethnoracial groups supported differences in tau pathology distribution and coexisting hippocampal sclerosis, which may impact biomarker studies.